TNFSF13B rs9514828 C>T Polymorphism is Associated with Incidence of Atherosclerosis and Therapeutic Outcomes in Patients with Systemic Lupus Erythematosus - Fajar DR; Rostinawati T; Hamijoyo L; Sahiratmadja E; Amalia R; Barliana MI (Biologics: Targets & Therapy, 2024)
Desi Reski Fajar,1,2 Tina Rostinawati,1 Laniyati Hamijoyo,3,4 Edhyana Sahiratmadja,4,5 Riezki Amalia,6,7 Melisa Intan Barliana1,7 1Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, Indonesia; 2Institut of Pelamonia Health Sciences, Makassar, Indonesia; 3Division of Rheumatology, Department of Internal Medicine, Faculty of Medicine, Universitas Padjadjaran / Hasan Sadikin General Hospital, Bandung, Indonesia; 4Immunology Study Center, Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia; 5Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Jatinangor, Indonesia; 6Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Jatinangor, Indonesia; 7Center of Excellence for Pharmaceutical Care Innovation, Universitas Padjadjaran, Jatinangor, IndonesiaCorrespondence: Melisa Intan Barliana, Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Ir. Soekarno KM 21, Jatinangor, 45363, Indonesia, Tel +6281214451177, Email melisa.barliana@unpad.ac.idBackground: Systemic lupus erythematosus (SLE) is a complex autoimmune disease with numerous clinical manifestations. Organ involvement can aggravate patients with SLE and cause comorbidities such as atherosclerosis. Recently, the TNFSF13B gene has been found to be linked with SLE events. This study aimed to analyze the association between single nucleotide polymorphisms of the TNFSF13B rs9514828 with incidence of atherosclerosis and therapeutic outcomes in patients with SLE.Patients and Methods: This case-control study included 84 SLE patients, of whom 21 patients with SLE with atherosclerosis and 63 patients with SLE without atherosclerosis. Using enzyme-linked immunosorbent assay method, interleukin-6 and interferon gamma levels were quantified. The TNFSF13B gene polymorphism was evaluated using polymerase chain reaction followed by sequencing. The lupus low disease activity state (LLDAS) criteria were used to measure the therapeutic outcomes. Statistical analysis was conducted using binary logistic regression.Results: The genetic variations of TNFSF13B rs9514828 were CC = 35, CT = 41, and TT = 8. There was an association between TNFSF13B rs9514828 C>T polymorphism in patients with SLE with and without atherosclerosis (p = 0.03; odds ratio (OR) 4.72, 95% confidence interval [CI] 1.22– 18.37). Furthermore, the TNFSF13B rs9514828 C>T polymorphism had association with the therapeutic outcomes of patients with SLE who manifested with LLDAS (p = 0.00; OR 7.58, 95% CI 2.61– 21.99).Conclusion: The association of TNFSF13B rs9514828 C>T polymorphism and incidence of atherosclerosis as well as the therapeutic outcomes in patients with SLE indicate the potential utility of the gene variation as screening tool to employ personalized medicine to undertake preventive measures in order to prevent atherosclerosis and to predict a poor prognosis in SLE patient.Keywords: systemic lupus erythematosus, atherosclerosis, genetic polymorphism, TNFSF13B, LLDAS